Beyond the template: the needs of tribal women and their experiences with maternity services in Odisha, India - Sana Q. Contractor; Abhijit Das; Jashodhara Dasgupta; Sara Van Belle (BMC, 2018)
Abstract Background Over the past 15 years, several efforts have been made by the Government of India to improve maternal health, primarily through providing cash incentives to increase institutional child birth and strengthen services in the public health system. The result has been a definite but unequal increase in the proportion of institutional deliveries, across geographical areas and social groups. Tribal (indigenous) communities are one such group in which the proportion of institutional deliveries is low. The persistence of these inequities indicates that a different approach is required to address the maternal health challenges in these communities. Methods This paper describes an exploratory study in Rayagada District of Odisha which aimed to understand tribal women's experiences with pregnancy and childbirth and their interactions with the formal health system. Methods included in-depth interviews with women, traditional healers and formal health care providers and outreach workers, observations in the community and health facilities. Results The exploration of traditional practices shows that in this community, pregnancy and childbirth is treated as part of a natural process, not requiring external intervention. There is a well-established practice of birthing in the community which also recognizes the need for health system interventions in case of high-risk births or complications. However, there has been no effort by the health system to build on this traditional understanding of safety of woman and child. Instead, the system continues to rely on incentives and disincentives to motivate women. Traditional health providers who are important stakeholders have not been integrated into the health system. Despite the immense difficulties that women face, however, they do access health facilities, but barriers of distance, language, cultural inappropriateness of services, and experiences of gross violations have further compounded their distrust. Conclusions The results of the study suggest a re-examining of the very approach to addressing maternal health in this community. The study calls for reorienting maternal health services, to be responsive to the requirements of tribal women, cater to their cultural needs, provide support to domiciliary deliveries, invest in building trust with the community, and preserve beneficial traditional practices.